Potensi Wisata Edukasi Berbasis Wisata Ramah Anak di Daya Tarik Wisata Desa Coklat Bali Tabanan - Sugiarti, Dian Pramita; Mahagangga, I Gusti Agung Oka; Romer, Krista S.; Paramitha, Komang Kesya Amanda (JURNAL DESTINASI PARIWISATA, 2022)
The condition of Bali tourism during the Covid-19 pandemic has become very concerning, on the one hand, the need for travel is very high but cannot be balanced with the fact of the opening and closing of tourist destinations. Some of the tourist destinations that were closed were used as an opportunity for managers to renovate managed tourist destinations to comply with CHSE standards. The current conditions have also provided new lessons for managers and tourists regarding the safety of traveling during a pandemic. Special interest tourism such as educational tours is currently in demand by family tourists who want to spend time with family and learn about the culture of local people. Bali Chocolate Village is Chocolate Village is a new tourist destination in Bali since October 2020. It is located in Cau Village, Marga District, Tabanan Regency. The founder of Chocolate Village is Dr. Ir. I Wayan Alit Artha Wiguna, M.Si. who built the tourist attraction of Chocolate Village. Chocolate Village began to be known for educational tours that can provide insight for child tourists about how the process of growing chocolate fruit to the process of making it. Chocolate Village is a favorite destination today by local tourists and residents. The founder of Chocolate Village is I Wayan Alit Artha Wiguna who wants to provide new educational tours for child tourists to learn new lessons about the chocolate-making process and educate tourists so that they get to know the chocolate tree which is one of the plantation plants in Indonesia. This child-friendly tourism-based educational tour is expected to: 1) Become a pilot for child-friendly tourist attractions. 2) Promote childfriendly based educational tourism in every attraction of educational tours. 3) There is a change in the perspective of visitors related to the benefits of educational tourism activities. The formulation of the problems to be raised is 1) The potential of Bali Chocolate Village as a child-friendly tourismbased educational tour 2) the existing condition of Bali Chocolate Village as a tour Child-Friendly Travel-Based Education Data were collected by observation, in-depth interviews, dissemination of questionnaires, literature studies, and documentation techniques. Data analysis techniques use descriptive qualitative and SWOT. The results of the identification of educational tourism are expected to be able to provide new knowledge in traveling, educational tourism activities can stimulate interest and creativity in children, increase children's motivation Amid a period of school saturation from home, increase the attitude of respect and care for the tourist destinations visited such as natural tourism by protecting the environment and forming closeness between families. Keywords: Bali Chocolate Village, Child-Friendly Tourism, Educational Tourism